PENSERTIPIKATAN TANAH YANG DILAKUKAN DILUAR HAK YANG DIMILIKI (MELANGGAR ASAS NEMO PLUS JURIS) - Anindita Tria Agustina, Bambang Eko Turisno*), Ana Silviana (Diponegoro Law Journal, 2013)
Currently the land is a treasure for people who have a high value because of its function as a source of people's lives, so that every inch of land is maintained until death. In some areas there are a number of cases of land registration is done by someone who is not entitled to the land (Violation of the principle of Nemo Plus Juris). One of the disputes of land ownership which is the object of this research is a civil legal case relating to the release of the certificate has no legal certainty examined and tried in the District Court Unaha between Plaintiffs and Defendants in District Court Decision No.3/ Pdt.G/ 2010 / PN.Unh.The purpose of this study was to determine the process that violates the principle of land certification of Nemo Plus Juris and to determine the legal protection given to the original land owners in land certification of which violates the principle of Nemo Plus Juris.Method of approach used in this study is normative juridical methods, specifications descriptive research with Analytics. Which is the object and the subject of this research is No.3/Pdt.G/2010/PN.Unh Court Decisions and Land Office officials Konawe. And Data Analysis Methods used are qualitative Normative.The results showed that the process carried out by soil certification of Alm.Sarmatiah (Defendant's wife) is a violation of the principle nemo plus juris. For in certification of Alm.Sarmatiah not have rights to the land dispute object because the object land dispute is not part of the division of the estate Alm.sarmatiah, so that certificates that arise on behalf Alm.Sarmatiah not have the force of law. Based on existing regulations that Indonesia adopts negative publicity that contains positive elements that the State gives legal protection to the rightful owner in this case is the plaintiff, in addition to deciding No.3/ Pdt.G/ 2010/ PN.Unh Court Decision objects that are entitled to the land dispute is the Plaintiff, that are considered by the judge in deciding the case in the presence of witnesses and expert witnesses who stated that Plaintiff most entitled to the land dispute object.